The Boston Game and the ISIS Match: Terrorism, Media, and Sport. (August 2016) - Galily, Yair; Yarchi, Moran; Tamir, Ilan; Samuel-Azran, Tal
The world is becoming largely interconnected. This notion has thought-provoking implications due to the fact that this interdependence affords terrorist organizations opportunities to perpetrate attacks. It is inevitable that an increased risk of terrorism, especially on the forefront of megasporting events, is on the rise due to the global publicity such attacks receive. This article focuses on the Boston Marathon Bombing and the Islamic State and illustrates how high-profile news coverage and coverage on social media (through user-generated content or "terrorist organization"–generated content) advance terrorist groups' attempts to use large-scale sporting events to leverage their agenda and ideology.